Private Participation in Infrastructure in Europe and Central Asia : A Look at Recent Trends - Vagliasindi, Maria; Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
This note asserts that Eastern Europe and Central Asia is attracting more investment to infrastructure projects with private participation than any other developing region except Latin America. Members of the European Union (EU) and countries seeking membership account for most of the investment. The Russian Federation is emerging as a leader both in attracting private activity and in sponsoring projects in neighboring countries. Telecommunications and energy are the leading sectors. But new regulatory challenges are emerging as a result of exclusivity periods in telecommunications and greater market concentration and vertical reintegration in energy.